DZYUDONÍŃ RAWAJLANÍW ТАRIYХÍNАN - Sultamuratov, Dj.; Aytmuratova, B. (ILIM hám JÁMIYET, 2022)
The article discusses the history of the emergence, formation and development of judo. Also, information about the history and future of judo sport in the Republic of Karakalpakstan, as well as the achievements of young judokas was presented.